Increased AID results in mutations at the CRLF2 locus implicated in Latin American ALL health disparities - Rangel, Valeria; Sterrenberg, Jason N.; Garawi, Aya; Mezcord, Vyanka; Folkerts, Melissa L.; Calderon, Sabrina E.; Garcia, Yadhira E.; Wang, Jinglong; Soyfer, Eli M.; Eng, Oliver S.; Valerin, Jennifer B.; Tanjasiri, Sora Park; et al. (Nature communications, 2024)
Activation-induced cytidine deaminase (AID) is a B cell-specific mutator required for antibody diversification. However, it is also implicated in the etiology of several B cell malignancies. Evaluating the AID-induced mutation load in patients at-risk for certain blood cancers is critical in assessing disease severity and treatment options. We have developed a digital PCR (dPCR) assay that allows us to quantify mutations resulting from AID modification or DNA double-strand break (DSB) formation and repair at sites known to be prone to DSBs. Implementation of this assay shows that increased AID levels in immature B cells increase genome instability at loci linked to chromosomal translocation formation. This includes the CRLF2 locus that is often involved in translocations associated with a subtype of acute lymphoblastic leukemia (ALL) that disproportionately affects Hispanics, particularly those with Latin American ancestry. Using dPCR, we characterize the CRLF2 locus in B cell-derived genomic DNA from both Hispanic ALL patients and healthy Hispanic donors and found increased mutations in both, suggesting that vulnerability to DNA damage at CRLF2 may be driving this health disparity. Our ability to detect and quantify these mutations will potentiate future risk identification, early detection of cancers, and reduction of associated cancer health disparities. Rates of Philadelphia chromosome-like (Ph-like) acute lymphoblastic leukemia (ALL) continue to rise in Hispanics and Latinos. Authors developed a digital PCR assay to quantify activation-induced cytidine deaminase activity at risk loci involved in cancer etiology that may contribute to this health disparity.